The Effect of Jeruju Leaf Brew (Acanthus ilicifolius L) on HOMA-IR and TNF-α in White Rats Induce by STZ-NA - Majdiyyah, Munifa; Chairina, Ade; Nur Afifah, Diana; Syauqy, Ahmad (Poltekkes Kemenkes Banjarmasin Jurusan Analis Kesehatan, 2025)
The International Diabetes Federation (IDF) has reported a consistent global rise in the prevalence of type 2 diabetes mellitus (T2DM). Conventional T2DM treatments such as metformin, sulfonylureas, and insulin therapy are effective. Still, they can lead to side effects, including gastrointestinal disturbances, hypoglycemia, renal impairment, weight gain, and complications associated with injection procedures. The herbal remedies are considered a natural alternative with fewer adverse effects. Acanthus ilicifolius (Jeruju) contains antioxidant compounds such as flavonoids, alkaloids, and saponins and may serve as a complementary therapy. This study investigated the effect of jeruju leaf brew at 6 ml/kg/day and 12 ml/kg/day on tumor necrosis factor alpha (TNF-α) and homeostatic model assessment of insulin resistance (HOMA-IR) levels. Using a true experiment with a randomized post-test only with a control group design, 30 rats were divided into five groups (K0, K−, K+, P1, and P2). After 28 days of intervention, groups P1 and P2 showed significant reductions in TNF-α (7.80 pg/ml and 6.94 pg/ml, respectively) and HOMA-IR (3.75 and 3.28, respectively). These findings indicate that a higher dose of jeruju leaf brew results in greater reductions in TNF-α and HOMA-IR levels in T2DM rats.